Influencia de cepas de Azotobacter en el cultivo de maíz bajo dos sistemas de labranza, en la zona de Puebloviejo, provincia de Los Ríos - González Maridueña, Jonathan Eduardo (2017)
VIII. SUMMARY In Mr. Jonathan's lands Gonzales located in the Km 35 of the road Babahoyo-Puebloviejo, was established a rehearsal in the hybrid corn DK-7088, in which was evaluated stumps of Azotobacter in the cultivation of corn low two farm systems. With this it was measured the effects of the doses of products on the agronomic behavior and an economic analysis of the grain yield in function at the cost of the treatments. The experimental design was used in divided parcels, with 2 treatments, 5 subtreataments and three repetitions. The variables were evaluated: days to flowering, plant height, height of ear insert, ears for plant, diameter of ears, longitude of ears, relationship grain/tusa, weight of ears, weigh of 100 grains and grain yield. The evaluated variables were subjected to the variancia analysis, and the test was applied from Tukey to 95% of probability to determine the statistical difference among the stockings of the treatments. Analyzed the experimental results, he found significant effects in agronomic several characteristics of the doses from complementary Azobacter to the fertilization soils. In what concerns to days to flowering and it harvests, statistical significancia was not reported among the treatments. The result of the applications of Azotobacter showed improvement of the physiologic and morphological conditions of the plantation, the cultivation it achieved an appropriate development, increasing the growth of the plants and the quality of the crop. The biggest grain yield you obtuvó with the system of farm reduced treaty with a dose of 1,0 L/ha of Azotobacter with a concentration of 1x108 UFC.